Lets check
47 times 7 is not equal to 315
47 times 5 =235
47 times 9 is not equal to 235
alishas speed is 47 mph
Answer:
it's the last one *25,000 J
Step-by-step explanation:
Answer:
Simplifying
x = -25
Step-by-step explanation:
Reorder the terms:
10x + -6(5 + 2x) = 20
10x + (5 * -6 + 2x * -6) = 20
10x + (-30 + -12x) = 20
Reorder the terms:
-30 + 10x + -12x = 20
Combine like terms: 10x + -12x = -2x
-30 + -2x = 20
Solving
-30 + -2x = 20
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '30' to each side of the equation.
-30 + 30 + -2x = 20 + 30
Combine like terms: -30 + 30 = 0
0 + -2x = 20 + 30
-2x = 20 + 30
Combine like terms: 20 + 30 = 50
-2x = 50
Divide each side by '-2'.
x = -25
Answer: The value of k for which one root of the quadratic equation kx2 - 14x + 8 = 0 is six times the other is k = 3.
Let's look into the solution step by step.
Explanation:
Given: A quadratic equation, kx2 - 14x + 8 = 0
Let the two zeros of the equation be α and β.
According to the given question, if one of the roots is α the other root will be 6α.
Thus, β = 6α
Hence, the two zeros are α and 6α.
We know that for a given quadratic equation ax2 + bx + c = 0
The sum of the zeros is expressed as,
α + β = - b / a
The product of the zeros is expressed as,
αβ = c / a
For the given quadratic equation kx2 - 14x + 8 = 0,
a = k, b = -14, c = 8
The sum of the zeros is:
α + 6α = 14 / k [Since the two zeros are α and 6α]
⇒ 7α = 14 / k
⇒ α = 2 / k --------------- (1)
The product of the zeros is:
⇒ α × 6α = 8 / k [Since the two zeros are α and 6α]
⇒ 6α 2 = 8 / k
⇒ 6 (2 / k)2 = 8 / k [From (1)]
⇒ 6 × (4 / k) = 8
⇒ k = 24 / 8
⇒ k = 3